Computed tomography analysis of sinonasal anatomical variations and relationship with the maxillary sinus retention cysts - Hamdi Kepekçi, Ahmet; Dizdar, Gökalp; Bestemi Kepekçi, Ali (ENT Updates, 2016)
Objective: The purpose of the present study was to investigate the relationship of sinonasal anatomic variations (SAVs) with maxillary sinus retention cysts (RCs) on paranasal sinus tomography. Methods: Our study included 202 patients who applied to the ENT outpatient clinic with fascial pain, nasal obstruction and postnasal drip complaints between September 2014 and February 2016 and underwent CT of paranasal sinus on coronal plane. The patients who had maxillary RCs in their CT scan comprised the study group while the patients who did not have RCs in their CT scan comprised the control group. The CT scans of these two groups were examined and recorded for the SAVs. The statistical analysis of the SAVs for these two groups was conducted using the Mann-Whitney U test. Results: The presence of septal deviation from SAVs and pneumatized uncinate in patients found to have maxillary sinus retention cyst was considered statistically significant (p<0.05). The sex in patients with right maxillary sinus RCs was considered statistically significant (p<0.05). The presence of pneumatized uncinate in patients with left maxillary sinus RCs was considered statistically significant (p<0.05). Conclusion: In our study, the statistical relationship between SAV and maxillary sinus retention cysts may show that SAVs may be effective in the etiology of maxillary sinus retention cysts. This result has to be verified by more detailed studies.